Entwicklung der Milcherzeugung in ausgewaḧlten Regionen Baden-Wur̈ttembergs - Prognose und kritische Entscheidungsfaktoren - Kathrin Rothfuß; Anke Zondler; Barbara Engler; Reiner Doluschitz (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2009)
– The abolition of the EU Milk Quota Regulation in 2015 will require milk producers to adapt. Their having to adapt is likely lead to structural changes both at regional level and at farm level. 411 milk producers in Baden-Wuerttemberg were surveyed in the course of the study (1 050 questionnaires, feedback 39 %). The main objective was to examine their likely reactions to the abolition of the milk quota regulation. The forecast shows that even in a favoured region for milk production, the overall output of milk could be reduced. Two groups of milk producers are compared by discriminant analysis. The farmers of the first group plan to quit milk production whereas the farmers of the second group intend to increase the output of milk. There is evidence that farm size alone is not the only discriminating factor in different regions, but that organisation on a sideline basis and the attitude of the farm operators also play a role.
Keywords: 330; Milchviehhaltung; Milchpolitik; Prognose; Diskriminanzanalyse; Baden-Württemberg